The effect of monosodium glutamate on the morphofunctional state of the thyroid gland in an experiment - Svyatoska , L.O. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. Clinical observations and numerous studies do not provide a clear answer regarding the safe dose of the food additive monosodium glutamate (MSG). The least studied is the effect of MSG on the thyroid gland. Objective. To evaluate the effect of prolonged consumption of monosodium glutamate on the morphofunctional state of the thyroid gland in adult male Wistar rats. Methods. The experimental study was conducted on 20 adult male Wistar rats of reproductive age, which received MSG in their diet at a dose of 0.07 g/kg with free access to water. The first group of animals was examined after 4 weeks of the experiment, and the morphofunctional state of the thyroid gland was assessed by determining hormone levels in the blood: free thyroxine (fT4) and pituitary thyroid-stimulating hormone (TSH). After 10 weeks of the experiment, the second group of animals was examined, with the same parameters evaluated as in the first group. Results. After 4 weeks of MSG administration, the thyrocytes, as in the control group, were cubic in shape, located on the basement membrane, forming the follicular wall. The nuclear chromatin was distributed homogeneously, the nuclei were basophilic, and the cytoplasm was oxyphilic. Interfollicular cells were present in the interfollicular connective tissue areas. The follicles were surrounded by capillaries and contained oxyphilic-stained colloid. In all areas of the thyroid gland, the follicles were filled with colloid, and lymphoid cell clusters were found in the interfollicular areas. TSH and fT4 levels were determined by radioimmunoassay. The TSH concentration was 0.66±0.11 mIU/L, and free thyroxine (fT4) was 20.26±0.82 pmol/L. At this stage, both values showed no significant deviations. After 10 weeks of the experiment, it was observed that peripherally located functional follicles contained preserved colloid; however, the amount was minimal, and it poorly absorbed the dye. The absence of colloid in the follicular lumen, along with uneven follicular walls with protrusions, was noted. Some thyrocytes were displaced into the follicular lumen, deforming their shape. The cell membrane was indistinct, and the nuclei showed signs of pyknosis. The interfollicular spaces contained diffusely distributed lymphocytes and macrophages. Large clusters of lymphoid cells were found in some areas. The TSH concentration was 0.08±0.02 mIU/L (p<0.001), and free thyroxine (fT4) was 30.8±1.51 pmol/L (p<0.001), indicating a marked hyperproduction of TSH and excessive synthesis of free thyroxine. Conclusion. Thus, the use of monosodium glutamate at the administered dose of 70 mg/kg during prolonged consumption promotes the development of thyroid pathology, significantly increasing the concentration of pituitary thyroid-stimulating hormone and causing a pronounced excess of free thyroxine.